Perancangan Vaksin Berbasis Epitop Sel B Untuk Penyakit Hepatitis B: B CELL EPITOP BASED VACCINE DESIGN FOR HEPATITIS B DISEASE - Toepak, Erwin Prasetya; Rey Kamala Dewi (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Palangka Raya, 2021)
Hepatitis B is a type of disease caused by infection with the hepatitis virus (HBV). HBV is a virus in the Hepadnaviridae family. This viral infection can cause clumping of liver cells, such as cirrhosis and hepatocellular carcinoma which if left untreated can lead to death. HBV itself has a non-structural protein polymerase that plays an important role in its life cycle. This in silico method is economical and effective for the discovery of new drugs by utilizing computer capabilities. In this study, the design of an epitope B-based vaccine from the HBV polymerase will be carried out. Hepatitis B polymerase sequences were obtained from the NCBI database site and then tested for antigenicity with the Vaxijen server. The results of the hepatitis B protein sequence antigenity test have a protective antigen value of 0.5783 so it is possible to use it as a vaccine candidate.